Correlation between trauma and injury severity score and prognosis in patients with trauma. Issue 6 (December 2021) - Chatimah, Chusnul; Pratiwi, Indah D.; Al Husna, Chairul H.
الملخص: أهداف البحث: تهدف هذه الدراسة إلى تحديد العلاقة بين درجة خطورة الإصابات والصدمات والتنبؤ بنتيجة مرضى الصدمات. طرق البحث: قمنا بتحليل ١٨٧ سجلا طبيا بأثر رجعي لمرضى الصدمات الذين قدموا إلى قسم الطوارئ في مركز الصدمات من المستوى الثاني في شرق جاوة ، إندونيسيا بين أغسطس وديسمبر ٢٠١٨. قمنا بتحليل البيانات بما في ذلك الخصائص الديموغرافية، ومقياس غلاسكو للغيبوبة، وضغط الدم الانقباضي ومعدل التنفس ودرجة الإصابة لستة أجزاء من الجسم. وتم استخدام اختبار ارتباط رتبة سبيرمان لتحديد الارتباط بين المتغيرات. النتائج: تمت مراجعة ما مجموعه ١٨١ سجلا طبيا لمرضى الصدمات في هذه الدراسة. كان ثلثا المرضى من الذكور (ن = ١١٣، ٦٢.٤٪). ما يقرب من نصف الإصابات الناجمة عن حوادث الطرق (ن = ٨٩، ٤٩.٢٪) ؛ نتجت غالبية هذه الإصابات عن صدمة حادة (ن = ١٦٧، ٩٢.٣٪). تراوحت درجات خطورة الإصابات والصدمات لمعظم المرضى (ن = ١٧٨، ٩٨.٣٪) مع تشخيص جيد بين ٧٧.١٪ - ٩٩.٧٪. كانت هناك علاقة ذات دلالة إحصائية بين الصدمات، ودرجات خطورة الإصابات والصدمات والتشخيص لمرضى الصدمات، مع ارتباط إيجابي بين المتغيرات. الاستنتاجات: كان هناك ارتباط معنوي بين درجات خطورة الإصابات والصدمات والتنبؤ بنتيجة مرضى الصدمات. Abstract: Objectives: This study aims to determine the correlation between Trauma and Injury Severity Score (TRISS) and prognosis in patients with trauma. Methods: We retrospectively analysed 187 medical records of patients with trauma who presented to the emergency department of a level II trauma centre in East Java, Indonesia, between August and December 2018. We analysed the data, which included demographic characteristics, Glasgow Coma Scale score, systolic blood pressure, respiratory rate, and injury scores of six parts of the body. Spearman's rank correlation was used to determine the correlation among variables. Results: A total of 181 medical records of patients with trauma were reviewed in this study. Two-third of the patients were male (n = 113, 62.4%). Approximately half of the trauma injuries were caused by road traffic accidents (n = 89, 49.2%); the majority of these injuries resulted from blunt trauma (n = 167, 92.3%). The TRISSes of most of the patients (n = 178, 98.3%) with a good prognosis ranged from 77.1% to 99.7%. There was a statistically significant correlation between trauma, TRISS, and prognosis ( p  = 0.002 < 0.05), with a positive correlation among variables (r = 0.225). Conclusion: There was a significant correlation between TRISS and prognosis in patients with trauma.